2004
DOI: 10.1086/422573
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Index and Quasi‐Periodic Oscillation Frequency Correlation in Black Hole Sources: Observational Evidence of Two Phases and Phase Transition in Black Holes

Abstract: Recent studies have shown that strong correlations are observed between the low frequencies (1-10 Hz) of quasi-periodic oscillations (QPOs) and the spectral power law index of several black hole (BH) candidate sources, in low (hard) states, steep power law (soft) states, and transitions between these states. The observations indicate that the X-ray spectra of such state (phases) show the presence of a power-law component and are sometimes related to simultaneous radio emission, indicating the probable presence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 49 publications
(51 reference statements)
11
107
0
Order By: Relevance
“…-Instabilities: Titarchuk and Fiorito, 2004 proposed the so called transition layer model, where type-C QPOs are the result of viscous magneto-acoustic oscillations of a spherical bounded transition layer, formed by matter from the accretion disc adjusting to the sub-keplerian www.an-journal.org boundary conditions near the central compact object. Cabanac et al, 2010 proposed a model to explain simultaneously type-C QPOs and the associated broad band noise.…”
Section: Type-b Qposmentioning
confidence: 99%
“…-Instabilities: Titarchuk and Fiorito, 2004 proposed the so called transition layer model, where type-C QPOs are the result of viscous magneto-acoustic oscillations of a spherical bounded transition layer, formed by matter from the accretion disc adjusting to the sub-keplerian www.an-journal.org boundary conditions near the central compact object. Cabanac et al, 2010 proposed a model to explain simultaneously type-C QPOs and the associated broad band noise.…”
Section: Type-b Qposmentioning
confidence: 99%
“…LF QPOs (below 10 Hz) were detected in many BHXBs during the low/hard and intermediate states, such as XTE J150−564 (e.g., Cui et al 1999;Sobczak et al 1999) and GX 339−4 (e.g., Miyamoto et al 1991;Motta et al 2011;Tamura et al 2012). Previous studies suggested that their frequencies are positively correlated with the photon index of the Comptonization below ≈10 Hz, at which the correlation saturates (Vignarca et al 2003;Titarchuk & Fiorito 2004;Titarchuk & Shaposhnikov 2005). Our results follow this ubiquitous correlation between the QPO frequency and the photon index; the photon index becomes lower by ≈0.03 in the ≈30% decrease of the QPO frequency.…”
Section: Origin Of Qpomentioning
confidence: 99%
“…Up to now, theoretical models of LFQPO have focused on type C LFQPO and tended to tie its frequency to a magnetoacoustical frequency (e.g. Titarchuk & Fiorito 2004) or to the Keplerian frequency at some radius in the disk (e.g. Tagger & Pellat 1999).…”
Section: Propertiesmentioning
confidence: 99%